Numerical Techniques for solving ordinary differential equations with uncertainty - Augus Kurian; I R Sumathi (Neutrosophic Sets and Systems)
In this article, we derive a numerical solution to the ordinary differential equation with a neutrosophic number as the initial condition.The Adams-Bashforth, Adams-Moulton, and predictorcorrector algorithms are used to solve the differential equation with hexagonal neutrosophic number as the initial condition. The convergence and stability of the methods are also investigated.